2020
DOI: 10.1101/2020.09.20.20198499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated serum uric acid is a facilitating mechanism for insulin resistance mediated accumulation of visceral adipose tissue

Abstract: BACKGROUND: Serum uric acid (SUA) has a relationship with cardiometabolic conditions such as insulin resistance (IR) and visceral adipose tissue (VAT) accumulation. Here, we aimed to clarify the nature of this relationship and the underlying causality mechanism. METHODS: We conducted a population-based cross-sectional study comprising 8,504 subjects joining both NHANES 2003-2004 and 2011-2012 cycles and ENSANUT Medio Camino 2016. We performed mixed effects linear regression models using HOMA2-I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It is widely believed that plasma levels of serum uric acid are negatively correlated with e-GFR and insulin sensitivity. 26,27 Herein, we provided more reliable evidence that the improved insulin sensitivity during GnRH therapy was at least partially attributable to the increased testosterone-related muscle mass, which acts as the primary source of purine and thereby leads to an upregulation of serum uric acid. Moreover, there is consistent evidence of the involvement of impaired insulin sensitivity in the development of renal dysfunction.…”
Section: Predictors Of Posttreatment Testosterone Levelsmentioning
confidence: 91%
“…It is widely believed that plasma levels of serum uric acid are negatively correlated with e-GFR and insulin sensitivity. 26,27 Herein, we provided more reliable evidence that the improved insulin sensitivity during GnRH therapy was at least partially attributable to the increased testosterone-related muscle mass, which acts as the primary source of purine and thereby leads to an upregulation of serum uric acid. Moreover, there is consistent evidence of the involvement of impaired insulin sensitivity in the development of renal dysfunction.…”
Section: Predictors Of Posttreatment Testosterone Levelsmentioning
confidence: 91%
“…Moreover, reactive oxygen species (ROS) generated during the formation of urate or from activation of NAD phosphate oxidase by urate also diminish insulin signaling [49]. Several studies have shown that increased HOMA-IR predicts hyperuricemia independent of dyslipidemia, hypertension, and/or obesity [53]. Moreover, slightly elevated serum urate concentrations may be beneficial by preserving the activity of superoxide dismutase 3, and AKT3/phosphoinositide 3 signaling regulates de novo and salvage purine nucleotide synthesis by regulating the production of phosphoribosyl diphosphate from glucose [53][54][55].…”
Section: Purines and Type 2 Diabetesmentioning
confidence: 99%
“…Several studies have shown that increased HOMA-IR predicts hyperuricemia independent of dyslipidemia, hypertension, and/or obesity [53]. Moreover, slightly elevated serum urate concentrations may be beneficial by preserving the activity of superoxide dismutase 3, and AKT3/phosphoinositide 3 signaling regulates de novo and salvage purine nucleotide synthesis by regulating the production of phosphoribosyl diphosphate from glucose [53][54][55]. Adenosine, a purine metabolite, is also known to regulate insulin-mediated glucose uptake and the decline of inosine monophosphate (IMP) dehydrogenase in diabetes was restored by insulin treatment, in animal studies [56 & ].…”
Section: Purines and Type 2 Diabetesmentioning
confidence: 99%